Investigação do óbito materno nas notificações do Near Miss Materno do Estado do Paraná - Pedroso, Brunna Pereira (2024)
Maternal mortality represents a serious global public health issue. It is defined as the death of a woman during pregnancy, childbirth, or within 42 days after the end of pregnancy. Reducing global maternal mortality to less than 70 deaths per 100,000 live births by 2030 is one of the Sustainable Development Goals (SDGs). However, the COVID-19 pandemic had a significant negative impact, increasing maternal mortality rates in many countries, including Brazil, where COVID-19 was responsible for a substantial proportion of deaths among pregnant and postpartum women. Maternal mortality reflects socioeconomic inequalities and unequal access to maternal healthcare. In this context, the World Health Organization developed the term "Near Miss Materno," defined as a case in which a woman nearly died but survived a complication during pregnancy, childbirth, or the postpartum period. The aim of this study was to verify the characteristics of women reported by the Near Miss Materno monitoring system in the State of Paraná, identifying which characteristics increase the likelihood of death. This is a quantitative cross-sectional study conducted with data from the Near Miss Materno notification and monitoring system of the State Health Department and notifications from the Mortality Information System, covering the period from January to December 2021. The sample consisted of 938 pregnant women reported in the NMM, which were compared with the Mortality Information System. It was found that 7.78% had death as an outcome due to the worsening of NMM complications. Among the women who progressed to death, 61.9% were white. The average age was 28.67 (SD 6.31) years. Regarding health conditions, 38.1% had no pre-existing clinical conditions. The average gestational week at the time of notification was 33.06 (SD 6.08), and 42.9% of the women were classified as high risk gestational. In the analysis of clinical criteria, diagnoses of septic shock and severe acute respiratory syndrome (SARS) or COVID-19 had 4.04 (CI 1.60 to 10.24; p-value: 0.17) and 10.07 (CI 4.96 to 20.47; p-value: <0.001) times higher likelihood of progressing to death, compared to other variables. When comparing the group of women who survived the NMM with those who died, there were statistically significant differences in the number of children, diagnosis of hemorrhagic diseases, hypertensive diseases, SARS, or COVID-19. In conclusion, the main causes of maternal death were associated with direct and indirect obstetric complications that were not prevented, controlled, or avoided. The worsening of NMM may have occurred due to interactions with COVID-19 or due to complications during pregnancy, childbirth, or the postpartum period, which may have been exacerbated by a lack of hospital beds, reduced ICU stay duration, or discharges to wards of patients who were still not fully free of risk, due to the COVID-19 pandemic, compromising care for pregnant and postpartum women. Regarding the investigation of maternal deaths in Paraná, this study highlights the need for improvements in maternal healthcare services and greater accuracy in the information recorded in the state’s notification system.